Use of fish scales as a tool for research - A Review - Neeraj Gupta (G-Journal of Environmental Science and Technology, 2017)
Various kinds of scales are found in fishes which are derived from the connective tissue of the dermis and form the exoskeleton. Scales of the fishes had been used as tool for experimental justifications. Structurally they are composed of circuli, radii, focal region and chromatophores region. Scales of fish are used for classification, identification and growth studies of different fishes, pollution indicators etc.